A new tool for studying waterfowl immune and metabolic responses: Molecular level analysis using kinome profiling. Issue 16 (30th July 2018) - Pagano, Giovanni; Johnson, Casey; Hahn, D. Caldwell; Arsenault, Ryan J.
Abstract: Here, we describe the design of an Anas‐ specific kinome peptide array that can be used to study the immunometabolic responses of mallard and American black duck to pathogens, contaminants, and environmental stress. The peptide arrays contain 2, 642 unique phosphorylate‐able peptide sequences representing 1, 900 proteins. These proteins cover a wide array of metabolic and immunological processes, and 758 Gene Ontology Biological processes are statistically significantly represented on the duck peptide array of those 164 contain the term "metabolic" and 25 "immune." In addition, we conducted a comparison of mallard to American black duck at a genetic and proteomic level. Our results show a significant genomic and proteomic overlap between these two duck species, so that we have designed a cross‐reactive peptide array capable of studying both species. This is the first reported development of a wildlife species‐specific kinome peptide array. Abstract : We describe the design and creation of a new molecular biology tool that characterizes immunometabolism of two sympatric, congeneric duck species (American black duck and mallard duck) that have shown markedly contrasting population trends in recent decades. This tool delineates cellular signaling mechanisms and can be used to characterize species' differences in physiological tolerance to experimental stimuli.